Young Woman with Unexplained Neutropenia and Neutrophils with Bilobed Nuclei: Marrow Findings - Barnes, Martin; Shklar, Victoria; Patel, Dipen; Staszewski, Harry (Case Reports in Hematology, 2023)
A 27-year-old female with a history of chronic sinusitis was referred for the evaluation of asymptomatic neutropenia. The differential demonstrated a mild neutropenia, which eventually resolved on subsequent evaluation. The liver and the spleen were not palpable. Peripheral flow cytometry was normal. Peripheral blood smear (PBS) demonstrated numerous Pelger–Huet anomalous neutrophils with characteristic “pince-nez” nuclei, without significant abnormalities in the other cell lines. Due to the benign clinical nature of hereditary PHA, a bone marrow biopsy is almost never required. However, our patient’s persistent and worsening neutropenia was unusual for hereditary PHA, so a bone marrow biopsy was performed to rule out MDS and leukemia. Our patient’s bone marrow smears showed dysplastic changes to other cell lines including the megakaryocytes and erythroid precursors. Due to our patient’s young age and concern that she may have a more serious marrow disorder, genetic testing was pursued. Germline testing in the LBR gene revealed a heterozygous pathogenic mutation, namely, the PR57837.17 variant, confirming the diagnosis of hereditary disease. The bone marrow biopsy performed on our patient illustrates that the presence of dysplasia does not rule out hereditary PHA and further genetic testing should be done in the appropriate clinical scenario. This case was an atypical presentation of hereditary PHA with confounding morphological features that would typically classify the disease as an acquired or pseudo-PHA, hence acting as a Pseudo-Pseudo-Pelger–Huet Anomaly.